PENGARUH PESAN KELOMPOK JURU PEMANTAU JENTIK (JUMANTIK) TERHADAP PERILAKU HIDUP BERSIH DAN SEHAT : (Studi Pada Kelurahan Ulujami) - Devi Septiana Putri (2021)
Background of the number of sufferers and the area of dengue dengue fever spread (DBD) is increasing in Indonesia over time. The Ministry of Health of the Republic of Indonesia has even made regulations related to the control of dengue hemorrhagic fever (DBD) regulated in the Decree of the Minister of Health No. 581/Menkes/SK/VII/1992 on the Eradication of Dengue Fever. One way of vector control can be done by applying healthy and clean living behavior (PHBS) together by recruiting residents around the community as a larva monitoring group (Jumantik).This group of larva monitors is tasked to conduct monitoring and counseling of mosquito larvae DBD in the homes of residents. The purpose of the study was to find out if there is an influence of the message conveyed by the larva monitoring group (Jumantik) in changing the behavior of the community in Ulujami Village to implement clean and healthy living behavior. The theory used symbolic interactions theory, interaction and symbols. The method used is quantitative method with explanative research type. The location of this research is in Ulujami Village. The population in the study was 10,951 heads of families (KK) using probability sampling techniques and Proportionate Stratified Random Sampling of 99 respondents. To determine the relationship and influence, the authors use the correlation test, the coefficient of determination test and hypothesis testing. The results of this study indicate that the results of the research hypothesis prove that Ho is rejected and Ha is accepted, so there is an effect of larva monitoring group (Jumantik) message on clean dan healthy living behavior (study in Ulujami village).